Evaluation of free radical scavenging capacity of methoxy containing-hybrids of thiosemicarbazone-triazole and their influence on glucose transport - Ademola O. Ayeleso; Jitcy S. Joseph; Oluwafemi O. Oguntibeju; Emmanuel Mukwevho (BMC, 2018)
Abstract Background Diabetes mellitus is a metabolic disease in which the body is unable to produce insulin or respond to insulin production, consequently leading to abnormal metabolism of carbohydrates, lipids and proteins causing elevation of glucose in the blood. Oxidative stress, an imbalance between the production of free radicals and body antioxidant system has been implicated in the pathogenesis of diabetes. Free radicals attack important macromolecules leading to cell damage. Antioxidants are intimately involved in the prevention of damage caused by free radicals. Methods The anti-diabetic effects of hybrid compounds (2a-h) of thiosemicarbazone and triazole containing methoxy groups at C (4) positions were tested against genes involved in glucose metabolism (Glut-4, Mef2a and Nrf-1) using quantitative real time PCR (qPCR). Free radical scavenging capacity (FRAP, TEAC, DPPH and ORAC) of the hybrids was also carried out by using established antioxidant capacity assays. Results From the results, hybrid compounds 2b and 2h showed more pronounced effects in up-regulating diabetes associated genes which are important in the up-regulation of glucose uptake. All the hybrid compounds also showed free radical scavenging abilities. Conclusion In conclusion, hybrid compounds (2b and 2h) can be useful as potential drugs for the management of diabetes mellitus.